2017
DOI: 10.22434/ifamr2014.0176
|View full text |Cite
|
Sign up to set email alerts
|

Governance structures in smallholder pig value chains in Uganda: constraints and opportunities for upgrading

Abstract: This paper analyses governance structures in Uganda’s smallholder pig value chains by applying the New Institutional Economics framework. It utilises cross sectional and qualitative survey data from randomly selected pig value chain actors in 4 districts. A multinomial logit model is applied to assess the determinants of vertical integration among pig traders. The findings indicate that most relationships at the pig production node of the value chain are based on spot market governance structures supported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 14 publications
1
63
0
Order By: Relevance
“…Choice experiments were originally used in communication and transport research [ 20 , 24 , 25 ]. Subsequently, they were adopted in other research areas such as environmental assessment [ 26 , 27 ], market research [ 28 , 29 , 30 ], plant and animal improvement programs [ 31 , 32 , 33 ], environmental and consumer studies [ 34 , 35 ] and, recently, in agricultural value chain research [ 36 , 37 , 38 ]. Choice experiments are based on Lancaster’s consumer behavior theory and McFadden’s random utility theory [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Choice experiments were originally used in communication and transport research [ 20 , 24 , 25 ]. Subsequently, they were adopted in other research areas such as environmental assessment [ 26 , 27 ], market research [ 28 , 29 , 30 ], plant and animal improvement programs [ 31 , 32 , 33 ], environmental and consumer studies [ 34 , 35 ] and, recently, in agricultural value chain research [ 36 , 37 , 38 ]. Choice experiments are based on Lancaster’s consumer behavior theory and McFadden’s random utility theory [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to Ouma et al (2017) access to market information is associated with high levels of market integration. Improved access to agricultural and market information usually leads to improvements in farming practices as a result of increased adoption of farm inputs.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…The social environment refers to the social dynamics (i.e., customs, norms and traditions) within communities of actors, and the social capital of the individuals influences collective actions (Jordaan et al, 2014). The institutional environment contains the rules and regulations for creating order to protect individuals against opportunistic behavior, it also encompasses the incentives for guiding the behavior of economic agents (Milagrosa, 2007;Ouma et al, 2017).…”
Section: A Short Overview Of Relevant Conceptual Frameworkmentioning
confidence: 99%
“…Inclusive business is a powerful way of helping drive economic opportunities for small-scale farmers, local and small agribusinesses, and the rural unemployed who would otherwise be left behind (Achterbosch et al, 2014). Ouma et al (2017) suggested that horizontal integration of smallholder pig producers in Uganda into collectives helps improve their bargaining power and reduce transaction costs. Knickel et al (2008) also demonstrated that European farmers benefit from collective action due to the growing power of retailers and the pressure resulting from the decline of producer prices and agricultural subsidies.…”
Section: Types Of Agri-food Chain Governance Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation